Household Transmission of Severe Acute Respiratory Syndrome Coronavirus-2 in the United States. (16th August 2020) - Lewis, Nathaniel M; Chu, Victoria T; Ye, Dongni; Conners, Erin E; Gharpure, Radhika; Laws, Rebecca L; Reses, Hannah E; Freeman, Brandi D; Fajans, Mark; Rabold, Elizabeth M; Dawson, Patrick; Buono, Sean; et al.
Abstract: Background: The evidence base for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is nascent. We sought to characterize SARS-CoV-2 transmission within US households and estimate the household secondary infection rate (SIR) to inform strategies to reduce transmission. Methods: We recruited patients with laboratory-confirmed SARS-CoV-2 infection and their household contacts in Utah and Wisconsin during 22 March 2020–25 April 2020. We interviewed patients and all household contacts to obtain demographics and medical histories. At the initial household visit, 14 days later, and when a household contact became newly symptomatic, we collected respiratory swabs from patients and household contacts for testing by SARS-CoV-2 real-time reverse-transcription polymerase chain reaction (rRT-PCR) and sera for SARS-CoV-2 antibodies testing by enzyme-linked immunosorbent assay (ELISA). We estimated SIR and odds ratios (ORs) to assess risk factors for secondary infection, defined by a positive rRT-PCR or ELISA test. Results: Thirty-two (55%) of 58 households secondary infection among household contacts. The SIR was 29% (n = 55/188; 95% confidence interval [CI], 23%–36%) overall, 42% among children (aged <18 years) of the COVID-19 patient and 33% among spouses/partners. Household contacts to COVID-19 patients with immunocompromised conditions and household contacts who themselves had diabetes mellitus had increased odds of infection with ORs 15.9 (95% CI, 2.4–106.9) and 7.1 (95% CI: 1.2–42.5), respectively. Conclusions: We found substantial evidence of secondary infections among household contacts. People with COVID-19, particularly those with immunocompromising conditions or those with household contacts with diabetes, should take care to promptly self-isolate to prevent household transmission. Abstract : Within US households, the severe acute respiratory syndrome coronavirus-2 secondary infection rate was 28%, with increased odds of infection for contacts of immunocompromised patients (odds ratio [OR], 18.1) and contacts with diabetes mellitus (OR, 7.8). People with coronavirus disease 2019 should promptly self-isolate to prevent transmission.